2021
DOI: 10.3390/su13105625
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization. A Review of the Risks Associated with the Inefficiency of Its Use and Policy Responses

Abstract: Nitrogen (N) is a key input to food production. Nearly half of N fertilizer input is not used by crops and is lost into the environment via emission of gases or by polluting water bodies. It is essential to achieve production levels, which enable global food security, without compromising environmental security. The N pollution level expected by 2050 is projected to be 150% higher than in 2010, with the agricultural sector accounting for 60% of this increase. In this paper, we review the status of the pollutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(63 citation statements)
references
References 133 publications
0
45
0
1
Order By: Relevance
“…1 Over the past 50 years, the use of nitrogen fertilizers increased almost eightfold. 2 However, the continuous growth of nitrogen fertilizers consumption is accompanied by growing emissions of ammonia – a major environmental contaminant that contributes to climate change, eutrophication, as well as to the acidification of water and soil which harms biodiversity. 3,4 In the atmosphere ammonia can react with other pollutants, such as nitrogen and sulfur oxides leading to the formation of particles, which create smog and have been linked to respiratory problems.…”
Section: Introductionmentioning
confidence: 99%
“…1 Over the past 50 years, the use of nitrogen fertilizers increased almost eightfold. 2 However, the continuous growth of nitrogen fertilizers consumption is accompanied by growing emissions of ammonia – a major environmental contaminant that contributes to climate change, eutrophication, as well as to the acidification of water and soil which harms biodiversity. 3,4 In the atmosphere ammonia can react with other pollutants, such as nitrogen and sulfur oxides leading to the formation of particles, which create smog and have been linked to respiratory problems.…”
Section: Introductionmentioning
confidence: 99%
“…Severe environmental problems can be originated by intensive dairy farming and its large amounts of LCM, which comprise a high content of organic matter, nitrogen, and phosphorous. The inappropriate management of LCM may result to eutrophication of water bodies [10], groundwater contamination [11], air pollution by the volatilization of ammonia, or other compounds and soil degradation [12] when manure is applied in excess [13].…”
Section: Introductionmentioning
confidence: 99%
“…Field studies have suggested that 30% of applied N in harvested crops is lost through leaching to groundwater as nitrate nitrogen (NO 3 − -N) [3]. Owing to the mobility of NO 3 − , such leaching often causes the contamination of shallow unconfined aquifers underlying agricultural lands [4]. Today, groundwater is estimated to supply 36% of drinking water globally, and the elevated concentrations of nitrate in drinking water sources often present a potential risk to public health.…”
Section: Introductionmentioning
confidence: 99%